APLIKASI SYSTEM MANAGEMENT TASK DAN PENILAIAN KERJA (KPI) PADA PT INTISOFT MITRA SEJAHTERA - Zega, Maria Ocktaviani; Chandrika, Desi; Siswanto, Ricki; Supardinah, Febrianti (Program Studi Teknik Informatika Fakultas Ilmu Komputer Univeristas Muslim Indonesia, 2018)
The purpose of this study is to create an application that can provide benefits to PT Intisoft Mitra Sejahtera in managing the tickets delivered by the client, arrange program modification policies, and can see the assessment of the performance of employees who work on the ticket and facilitate the client in obtaining quick information about obstacles which they experience by turning it into a ticket on the application. The research method used is by conducting an analysis (walking system survey, interview, and observation) and design method (UML), testing method (Black box testing). The analysis is carried out by conducting field studies and conducting interviews with the Director of PT Intisoft Mitra Sejahtera along with related divisions in the plan for making this application. The results achieved are web and android applications that function to manage work assignments and assessments that can help oversee, and document problems that exist in the company and also assess employee performance in handling reports of problems reported by the client.